Improved lignocellulose degradation efficiency based on Fenton pretreatment during rice straw composting. (December 2019) - Wu, Di; Wei, Zimin; Zhao, Yue; Zhao, Xinyu; Mohamed, Taha Ahmed; Zhu, Longji; Wu, Junqiu; Meng, Qingqing; Yao, Changhao; Zhao, Ran
Graphical abstract: Highlights: Fenton pretreatment changed structure changes of the raw materials. Part of lignocellulose-degrading enzymes were enhanced by Fenton pretreatment. Key enzymes and environmental factors have been identified by RDA and SEMs. Lignocellulose degradation efficiency was improved by Fenton pretreatment. Abstract: This study aims to explore the effect of Fenton pretreatment on organic fractions, enzymes activities and microbial communities during composting. In this study, rice straw was chosen to be composted after pretreatment. The results indicated that Fenton pretreatment significantly increased the degradation of organic matter and coarse fiber contents, which might be the reason that Fenton pretreatment enhanced lignocellulose-degrading enzymes activities during composting, including CMCase, FPase, xylanase, manganese peroxidase, lignin peroxidase and laccase. Additionally, Fenton pretreatment reshaped bacteria community. The key enzymes and environmental factors, which affected organic fractions degradation were identified by redundancy analysis. Furthermore, structural equation modeling and variation partitioning analysis further revealed possible mechanisms of organic fractions degradation in different treatments during composting. In summary, the combined application Fenton pretreatment and composting improved lignocellulose degradation efficiency, which provided for an effective and environment-friendly way to manage lignocellulose wastes.